Pengaruh Dua Gaya Mengajar Mosston dan Dukungan Motor Ability Mahasiswa Terhadap Hasil Belajar Teknik Dasar Sepak Takraw - Zulkifli; Yani, Ahmad; Kamarudin; Sasmarianto; Alficandra; Henjilito, Raffly (UIR Press, 2020)
This study aims to determine the effect of applying the teaching style of practice and inclusive teaching style on groups of students who have high and low motor abilities in the process of learning the basic techniques of sepak takraw. This research method uses experiments factorial 2x2 with by level design, the population of this study was 82 students of physical education study programs at the Riau Islamic University. The sample of this study was 44 people taken using purposive sampling technique, consisting of 22 people with high motor ability and 22 people with low motor ability. Furthermore the sample was divided into four groups of 11 people each. The data analysis technique used ANAVA with the results of the t-dunnet advanced test. (1) For students who have a high motor ability, the results of the learning of the takraw basic techniques of teaching practice style groups are better than inclusi teaching styles, with t0 = 5.06 ≥ ttable 1.67 then H0 is rejected. (2) Students who have low motor ability, the results of the learning of the basic techniques of takraw group inclusi teaching style is better than the teaching style of practice, with t0 = -1.81 ≤ ttable 1.67 then H0 is rejected. (3) There is an interaction between teaching style and motor ability on the results of the basic takraw learning techniques, with p-value = 0,000 ≤ 0.05 or H0 rejected.